Structural studies in lead germanate glasses: EXAFS and vibrational spectroscopy - Ribeiro, S.J.L [UNESP]; Dexpert-Ghys, J; Piriou, B; Mastelaro, V.R (Elsevier, 1993)
The Raman, IR absorption and EXAFS spectra at the Ge K-edge and Pb LIII-edge of eight lead germanate glasses, with general formula xPbO(1-x)GeO2 with x = 0.20, 0.25, 0.33, 0.40, 0.50, 0.53, 0.56 and 0.60, have been measured. The occurrence of [GeO6] units besides [GeO4] could not be deduced unambiguously from the data. The vibrational and EXAFS data agree with a progressive depolymerization of the network. Starting from all Ge atoms linked to four bridging oxygens in GeO2 (x = 0), the number of tetrahedral units with one or two non-bridging oxygens increases with x. At low content, Pb2+ ions act as modifiers in the germanate structure, but to a lesser extent than an equivalent number of alkaline ions. © 1993.
Keywords: Atoms; Ions; Light absorption; Molecular structure; Oxygen; Alkaline ions; Bridging oxygen; Depolymerization; Lead germanate glasses; Nonbridging oxygens; Glass